The adjuvant effect of bacterium-like particles depends on the route of administration - Sudo, Haruka; Tokunoh, Nagisa; Tsujii, Ayato; Kawashima, Sarana; Hayakawa, Yuta; Fukushima, Hiroki; Takahashi, Keita; Koshizuka, Tetsuo; Inoue, Naoki (Frontiers in Immunology, 2023)
Direct administration of vaccines to mucosal surfaces, such as via oral or nasal vaccination, represents an attractive alternative, or complement, to current parenteral vaccination because it has a potential to induce antigen-specific immunity both at mucosal and systemic tissues. Although bacterium-like particles (BLPs), peptidoglycan structures derived from lactic acid bacteria, have been investigated as a novel adjuvant for oral or nasal vaccines, it remains unclear whether the administration routes differ the adjuvant effect of BLPs. Here, we showed that the adjuvant effect of BLPs from Lactococcus lactis NZ9000 is greater with the nasal administration than with the oral administration. We conjugated BLPs with Tir, a virulence factor of Citrobacter rodentium, as a model adjuvant-antigen complex, and found that nasal, but not oral, immunization of mice with BLP-Tir induced robust antigen-specific IgA responses at the respiratory and intestinal mucosa, IgG2b-skewed systemic responses, and Th17 cellular responses. As one of the underlying mechanisms, we demonstrated that the nasal administration has a greater delivery efficiency (~1,000-fold) of the BLPs-conjugated antigens to mucosal-associated lymphoid tissues than the oral administration. Furthermore, the nasal, but not oral, administration of BLP-Tir elicited robust innate immune responses that were characterized by the expression of various pro-inflammatory cytokines and chemokines in the mucosal-associated lymphoid tissues. Considering these findings together, we anticipate that BLPs can be an attractive novel adjuvant for nasal vaccines targeting not only respiratory but also gastrointestinal infectious diseases.